Elastohydrodynamics Lubrication for Bio-Based Lubricants in Elliptical Conjunction - Zakaria, Nazri Huzaimi; Mohamad Zin, Mohd Rody; Abdollah, Mohd Fadzli bin; Saleman, Abdul Rafeq; Amiruddin, Hilmi; tamaldin, noreffendy (2014)
This paper investigates a bio-based lubrication issue of elastohydrodynamic lubricants in mechanical part. Bio-based lubricants are one of the possibilities that might be used as a substitute for the conventional lubricants in the industries. The paper focused on elastohydrodynamic lubrication flows at the elliptical conjunctions by using bio-based lubricants and mineral oil. The computational fluid dynamic was used to determine the effect of lubricants in elliptical conjunctions. This software helps to verify the deformation of the pressure distribution at the conjunctions. From this study, at constant speed, the mineral oil has higher value of dynamic pressure than bio-based lubricants along X and Y axis between two mating surfaces. It is found that, the mineral oil carried more load compared to bio-based lubricant. Hence, the bio-based lubricant is the best lubricant to protect the surfaces from wear and damage due to its properties has less value of dynamic pressure than mineral oil.